Hearing preservation outcomes with motorized cochlear implant electrode insertion: matched-cohort observations - Oetiker, Yannik; Aebischer, Philipp; Caversaccio, Marco; Mantokoudis, Georgios; Weder, Stefan (Frontiers in Surgery, 2025)
BackgroundCochlear implants (CIs) are an established treatment for severe sensorineural hearing loss and are increasingly used in patients with substantial residual hearing. Preservation of residual hearing is associated with improved outcomes, including speech understanding in noise, natural sound perception, and spatial hearing. Manual electrode insertion, however, is limited by hand tremor and abrupt maneuvers, which can cause intracochlear trauma. Motorized insertion tools (MITs) have been developed to enable slow, continuous, and highly controlled electrode advancement.MethodsWe conducted the first clinical evaluation of the OTOARM/OTODRIVE MIT system. Twenty-six patients underwent implantation with lateral wall electrodes using MIT and were compared with a matched retrospective cohort who received manual insertion. Surgical workflow integration, electrode positioning, residual hearing, speech comprehension, and patient-reported outcome measures (PROMs) were assessed at 1 and 6 months postoperatively.ResultsMIT integration into the surgical routine was feasible without major workflow disruptions. Angular insertion depth and electrode positioning did not differ significantly between groups. Patients with favorable preoperative hearing showed slightly better postoperative low-frequency pure tone thresholds in the MIT group, although statistical significance was not reached. Speech comprehension outcomes were comparable between groups. PROMs indicated greater gains in several subscales for the MIT-assisted cohort, despite incomplete data and limited statistical power.ConclusionMIT-assisted cochlear implantation was feasible and demonstrated a tendency toward improved hearing preservation and subjective benefit. However, the small sample size, retrospective controls, and incomplete PROM data limit definitive conclusions. Larger, blinded and randomized trials are needed to determine the clinical value of MIT systems for both objective and patient-reported outcomes.